Jonathan CRARY, What Does Climate Change Have to Do With the Internet? Scorched Earth – Beyond the Digital Age to a Post-Capitalist World, 2022 - Alina NOVEANU (Studia Universitatis Babeș-Bolyai. Philosophia)
Among those who agree to become active in the face of the real catastrophe that is global warming, reducing one's carbon footprint is the most sensible thing to do, and there are several guides on how to do it more effectively. Activism to force political commitment to environmental protection measures is increasingly visible after the pandemic: demonstrations, protests and strikes are being organized in cities around the world, and anyone can follow these actions on social media. Sustainability must be ensured for any new development, often combined with new opportunities for economic growth through investment in green industries. But degrowth is also becoming a more popular concept, even though it has yet to find its way outside the academic discourse and into economic practice. However, people everywhere in the world have experienced ecological catastrophes caused by rapid forced industrialization, the destruction of arable land, the replacement of traditional agriculture with large monocultures, the immense pollution in so-called industrial cities, and the failure of nuclear power plants. From this perspective, one might think that the new global we today is on a good path. In this scenario, too, the Internet and the rapid exchange on social media would be the ideal basis for organizing and acting together. In order to stop this social engagement, all oppressive regimes would attack this very medium, restrict user access, shut down websites, or delete information aimed at revealing facts hidden from the public.